Nutrition and exercise concerns of middle age - Driskell, Judy A. [ (Judy Anne)] (CRC Press, 2009)
Addresses the specific nutritional and physical activity needs of active individuals thirty to sixty years old. This title explores the role of diet and physical activity in reducing the risk of and in treating age-related diseases such as cancer and cardiovascular disease. It is suitable for nutritionists, physicians, dieticians, and researchers.